Silicon-based negative electrode material for all-solid-state battery as well as preparation method and application of silicon-based negative electrode material
Through high-temperature annealing treatment of silicon and lithium tetrafluoroborate, a silicon-based composite material with a multiphase mixture of Si, LiF, and LiBO2 was prepared, which solved the problem that the silicon-based negative electrode could not operate stably without external pressure, and achieved long-term stable operation and high-efficiency energy density in all-solid-state batteries.
Patent Information
- Application Number
- CN202510154616.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-02-12
AI Technical Summary
The silicon-based negative electrode is difficult to operate stably in a sulfide all-solid state battery without external pressure, resulting in rapid attenuation of battery performance.
By chemically reacting silicon and lithium tetrafluoroborate under high temperature annealing conditions, a silicon-based composite material with a multiphase mixture of Si, LiF, and LiBO2 was prepared. This material suppresses the volume effect of silicon and the loss of lithium ions through the electrochemical stability of LiF and the lithium loss of LiBO2.
It achieves long-term and stable operation of silicon-based anode material in all-solid-state batteries without external pressure, with the first Coulomb efficiency reaching 89.7%, and maintaining a high reversible capacity under different current densities.
Smart Images

Figure CN119627087A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of all-solid-state battery preparation, and in particular to a silicon-based negative electrode material for an all-solid-state battery, and a preparation method and application thereof. Background Art
[0002] All-solid-state lithium-ion batteries, with their high energy density, excellent safety performance and long cycle life, are gradually becoming the core research and development direction of the next generation of energy storage systems. Compared with traditional liquid lithium-ion batteries, all-solid-state batteries use solid electrolytes instead of liquid electrolytes, which fundamentally eliminates the risks of electrolyte leakage and battery explosion, greatly improving battery safety.
[0003] In the field of solid electrolytes, sulfide solid electrolytes have attracted much attention due to their excellent ionic conductivity and good mechanical properties. Sulfide solid electrolytes not only exhibit high ionic conductivity at room temperature and effectively promote the migration of lithium ions, but also form good interface contact with positive and negative electrode materials, reduce interface resistance, and thus improve the overall performance of the battery. Therefore, sulfide solid electrolytes are regarded as one of the key materials for realizing high-performance all-solid-state lithium-ion batteries.
[0004] Silicon (Si) is regarded as the most promising negative electrode material in all-solid-state lithium-ion batteries because of its theoretical capacity of up to 4200 mAh / g, which is much higher than that of graphite negative electrode, and its abundant resources and low cost. In particular, in sulfide all-solid-state lithium-ion batteries, the application of silicon-based negative electrodes is expected to significantly increase the energy density of batteries and promote technological innovation in the fields of electric vehicles, energy storage systems, etc.
[0005] However, the practical application of silicon-based anodes in sulfide all-solid-state batteries faces many challenges. Among them, the volume effect of silicon is particularly prominent. During the charge and discharge process, the volume of silicon changes significantly, leading to the destruction of the electrode structure and the rapid decay of battery performance. In order to limit the volume effect of silicon and maintain good interface contact, the traditional practice is to apply a higher stacking pressure to the battery. However, this high-pressure condition not only increases the manufacturing cost and difficulty of use of the battery, but also limits the energy density and cycle life of the battery system.
[0006] So far, although researchers have made significant progress in the modification of silicon-based anodes and the optimization of the interface between electrolytes and anodes, most studies on silicon-based anodes in sulfide all-solid-state batteries still require an external pressure of more than 50 MPa to achieve stable operation. This high-pressure condition seriously hinders the large-scale application of silicon-based anodes in all-solid-state batteries.
[0007] Therefore, how to prepare a silicon-based negative electrode material that can operate stably without external pressure has become a key issue that needs to be solved in the current field of all-solid-state lithium-ion batteries. This requires not only in-depth research on the failure mechanism of silicon-based negative electrodes in sulfide all-solid-state batteries, but also the exploration of new material preparation methods and structural design strategies to achieve the optimization and stabilization of silicon-based negative electrode performance. By comprehensively applying knowledge from multiple disciplines such as materials science, electrochemistry, and engineering technology, it is expected to open up new paths for the large-scale application of silicon-based negative electrodes in all-solid-state batteries. Summary of the invention
[0008] The purpose of the present invention is to solve the difficult problem that the silicon negative electrode is difficult to operate stably in a sulfide all-solid-state battery without external pressure. A silicon-based negative electrode material with high first coulombic efficiency and stable structure is prepared, which realizes long-term stable operation in the all-solid-state battery.
[0009] The present invention uses silicon (Si) and lithium tetrafluoroborate (LiBF4) to react chemically through high temperature annealing to obtain a multiphase mixed silicon-based composite material of Si, LiF, and LiBO2. LiF is derived from the thermal decomposition of LiBF4, and LiBO2 is the oxide layer (SiO x ) product of thermal reaction. Electrochemically stable and high Young's modulus LiF can inhibit the decomposition of Li6PS5Cl electrolyte and limit the volume effect of silicon, and LiBO2 can compensate for the lithium loss of silicon during the charge and discharge process. Therefore, the modified Si-based anode can achieve stable operation in all-solid-state batteries without external pressure.
[0010] To achieve the above-mentioned purpose, the technical solution of the present invention is as follows: The present invention provides a method for preparing a silicon-based negative electrode material for an all-solid-state battery, comprising the following steps: (1) mixing silicon and lithium tetrafluoroborate in a certain proportion to obtain a mixture; (2) The mixture in step (1) is subjected to high temperature annealing treatment under the protection of an inert gas to obtain a silicon-based negative electrode material.
[0011] Preferably, in step (1), the molar ratio of silicon to lithium tetrafluoroborate is 5-20:1.
[0012] More preferably, the molar ratio of silicon to lithium tetrafluoroborate is 12:1.
[0013] Preferably, in step (2), the temperature of the high temperature annealing treatment is 400-1200° C., and the time of the high temperature annealing treatment is 1-10 hours.
[0014] More preferably, the temperature of the high temperature annealing treatment is 800° C., and the time of the high temperature annealing treatment is 5 hours.
[0015] The present invention also provides a silicon-based negative electrode material prepared by the preparation method.
[0016] The present invention also provides the use of the silicon-based negative electrode material or the silicon-based negative electrode material prepared by the preparation method in an all-solid-state lithium-ion battery.
[0017] The present invention also provides a negative electrode sheet for an all-solid-state battery, wherein the negative electrode sheet comprises the silicon-based negative electrode material.
[0018] The present invention also provides a method for preparing the negative electrode sheet for the all-solid-state battery, comprising the following steps: The silicon-based negative electrode material as an active material, the electrolyte Li6PS5Cl, the conductive agent and the binder are weighed in a certain proportion, dispersed in an organic solvent, and mixed to prepare a slurry; the slurry is coated on a metal foil, and dried to obtain a negative electrode sheet; The mass ratio of the active material, electrolyte, conductive agent and binder is 30-80:10-50:5-30:1-5.
[0019] The conductive agent may be carbon nanofiber grown in the vapor phase, the binder may be ethyl cellulose, and the organic solvent may be anhydrous ethanol.
[0020] The present invention also provides an all-solid-state battery, comprising a lithium positive electrode sheet, an electrolyte Li6PS5Cl and a negative electrode sheet, wherein the negative electrode sheet comprises the negative electrode sheet for the all-solid-state battery.
[0021] The present invention also provides an assembly method of an all-solid-state battery, comprising: placing the electrode sheet in a mold; Add an appropriate amount of electrolyte Li6PS5Cl to the electrode sheet and compact it at a pressure of 20MPa for 1 minute; A lithium positive electrode sheet is placed on top of the electrolyte and compacted with a pressure of 1MPa to form a three-layer structure battery cell; the battery cell is assembled in a 2032-type button battery case for constant current charge and discharge test. During the constant current charge and discharge test, the battery has no external pressure and only operates on the internal pressure of the battery.
[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) The preparation method of the present invention is simple, and a Si-based composite material of an integrated multiphase composite of Si, LiF and LiBO2 is prepared by one-step annealing.
[0023] (2) LiF and LiBO2 in the Si-based composite material prepared by the present invention exhibit a unique synergistic effect. The electrochemically stable and high Young's modulus LiF can inhibit the decomposition of the Li6PS5Cl electrolyte and limit the volume effect of silicon, while LiBO2 can compensate for the lithium loss of silicon during the charging and discharging process.
[0024] (3) The structurally stable silicon-based composite material prepared by the present invention exhibits a high first coulombic efficiency of 89.7% in an all-solid-state lithium-ion battery and can operate stably without external pressure. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the X-ray diffraction pattern (XRD) of the F-Si powder prepared in Example 1.
[0026] Figure 2 This is a transmission electron microscope (TEM) image of the F-Si powder prepared in Example 1.
[0027] Figure 3 This is the first charge and discharge curve of the F-Si electrode prepared in Example 1.
[0028] Figure 4 The cycle performance of the F-Si electrode prepared in Example 1 at different current densities; wherein (a) is 0.05 Ag -1 Cycling performance at current density; (b) 0.1 A g -1 Cycling performance at different current densities. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below with reference to specific embodiments, but the protection scope of the present invention is not limited thereto.
[0030] Example 1
[0031] Si powder and LiBF4 powder were uniformly mixed in a molar ratio of 12:1 and placed in a tube furnace. After annealing at 800°C for 5 hours in an inert gas atmosphere, a Si-based composite material was obtained, named F-Si.
[0032] The X-ray diffraction pattern and transmission electron microscope image of F-Si powder are as follows Figure 1 and Figure 2 As shown, Figure 1 The X-ray diffraction pattern shows that the F-Si powder is mainly composed of Si and LiF. Figure 2 The transmission electron microscope image further confirmed the presence of Si and LiF, and also found the presence of LiBO2 in the F-Si powder, which indicated that the F-Si powder was composed of a three-phase composite of Si, LiF and LiBO2.
[0033] Active material F-Si, electrolyte Li6PS5Cl, conductive agent vapor-grown carbon nanofibers and binder ethyl cellulose were weighed in a mass ratio of 40:40:15:5, and slurry was prepared with anhydrous ethanol as solvent. The evenly mixed slurry was coated on copper foil and dried to obtain a 12 mm negative electrode sheet.
[0034] The negative electrode sheet was placed in a mold, and about 120 mg of Li6PS5Cl electrolyte was added. The negative electrode sheet was compacted at 20 MPa for 1 minute, and the lithium sheet was placed in the mold and compacted again at 1 MPa. The cold-pressed three-layer structure cell was taken out and assembled in a 2032 button cell.
[0035] Example 2
[0036] Si powder and LiBF4 powder were uniformly mixed in a molar ratio of 12:1 and placed in a tube furnace. After annealing at 1200°C for 10 hours in an inert gas atmosphere, a Si-based composite material was obtained, named F-Si.
[0037] Active material F-Si, electrolyte Li6PS5Cl, conductive agent vapor-grown carbon nanofibers and binder ethyl cellulose were weighed in a mass ratio of 50:30:10:10, and slurry was prepared with anhydrous ethanol as solvent. The evenly mixed slurry was coated on copper foil and dried to obtain a 12 mm negative electrode sheet.
[0038] The negative electrode sheet was placed in a mold, and about 120 mg of Li6PS5Cl electrolyte was added. The negative electrode sheet was compacted at 20 MPa for 1 minute, and the lithium sheet was placed in the mold and compacted again at 1 MPa. The cold-pressed three-layer structure cell was taken out and assembled in a 2032 button cell.
[0039] Example 3
[0040] Si powder and LiBF4 powder were uniformly mixed in a molar ratio of 5:1 and placed in a tube furnace. After annealing at 400°C for 1 hour in an inert gas atmosphere, a Si-based composite material was obtained, named F-Si.
[0041] Active material F-Si, electrolyte Li6PS5Cl, conductive agent vapor-grown carbon nanofibers and binder ethyl cellulose were weighed in a mass ratio of 60:25:15:5, and slurry was prepared with anhydrous ethanol as solvent. The evenly mixed slurry was coated on copper foil and dried to obtain a 12 mm negative electrode sheet.
[0042] The negative electrode sheet was placed in a mold, and about 120 mg of Li6PS5Cl electrolyte was added. The negative electrode sheet was compacted at 20 MPa for 1 minute, and the lithium sheet was placed in the mold and compacted again at 1 MPa. The cold-pressed three-layer structure cell was taken out and assembled in a 2032 button cell.
[0043] Example 4
[0044] Si powder and LiBF4 powder were uniformly mixed in a molar ratio of 20:1 and placed in a tube furnace. After annealing at 1200°C for 1 hour in an inert gas atmosphere, a Si-based composite material was obtained, named F-Si.
[0045] Active material F-Si, electrolyte Li6PS5Cl, conductive agent vapor-grown carbon nanofibers and binder ethyl cellulose were weighed in a mass ratio of 70:20:5:5, and slurry was prepared with anhydrous ethanol as solvent. The evenly mixed slurry was coated on copper foil and dried to obtain a 12 mm negative electrode sheet.
[0046] The negative electrode sheet was placed in a mold, and about 120 mg of Li6PS5Cl electrolyte was added. The negative electrode sheet was compacted at 20 MPa for 1 minute, and the lithium sheet was placed in the mold and compacted again at 1 MPa. The cold-pressed three-layer structure cell was taken out and assembled in a 2032 button cell.
[0047] Test Example 1
[0048] The first charge-discharge curve of the F-Si electrode prepared in Example 1 is as follows: Figure 3 As shown, the test voltage range is 0.01-2V and the current density is 0.05 A g -1 During the battery test, there was no external pressure, and only the built-in pressure of the battery was relied upon. The F-Si electrode showed a high first coulombic efficiency of 89.7%, meeting the needs of industrialization.
[0049] The cycling performance of the F-Si electrode prepared in Example 1 at different current densities is shown in FIG. Figure 4 As shown, the test voltage range is 0.01-2 V, and the current density is (a) 0.05 A g -1 and (b) 0.1 A g -1 During the battery test, there is no external pressure, only the internal pressure of the battery. -1 The reversible capacity is as high as 1752 mA hg after 50 cycles at the current density -1 , at 0.1 A g -1 The reversible capacity is as high as 1087 mA h g after 120 cycles at the same current density. -1This research has gotten rid of the dependence on external stacking pressure during the operation of Si-based all-solid-state batteries and achieved stable operation without external pressure.
[0050] The above only lists the preferred embodiments of the present invention, and the protection scope of the present invention is not limited thereto. Any changes made by those skilled in the art within the scope of the claims of the present invention shall fall within the protection scope of the present invention.
Claims
1. A method for preparing a silicon-based negative electrode material for an all-solid-state battery, characterized in that: The following steps are involved: (1) mixing silicon and lithium tetrafluoroborate in a certain proportion to obtain a mixture; (2) The mixture in step (1) is subjected to high temperature annealing treatment under the protection of an inert gas to obtain a silicon-based negative electrode material.
2. The method for preparing a silicon-based negative electrode material for an all-solid-state battery according to claim 1, characterized in that: In step (1), the molar ratio of silicon to lithium tetrafluoroborate is 5-20:
1.
3. The method for preparing a silicon-based negative electrode material for an all-solid-state battery according to claim 2, characterized in that: The molar ratio of silicon to lithium tetrafluoroborate is 12:
1.
4. The method for preparing a silicon-based negative electrode material for an all-solid-state battery according to claim 1, characterized in that: In step (2), the temperature of the high temperature annealing treatment is 400-1200° C., and the time of the high temperature annealing treatment is 1-10 hours.
5. The method for preparing a silicon-based negative electrode material for an all-solid-state battery according to claim 4, characterized in that: The temperature of the high temperature annealing treatment is 800° C., and the time of the high temperature annealing treatment is 5 hours.
6. The silicon-based negative electrode material prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the silicon-based negative electrode material according to claim 6 in an all-solid-state lithium-ion battery.
8. A negative electrode sheet for an all-solid-state battery, characterized in that: The negative electrode sheet comprises the silicon-based negative electrode material according to claim 6.
9. The method for preparing the negative electrode sheet for the all-solid-state battery according to claim 8, characterized in that: The following steps are involved: The silicon-based negative electrode material as an active material, the electrolyte Li6PS5Cl, the conductive agent and the binder are weighed in a certain proportion, dispersed in an organic solvent, and mixed to prepare a slurry; the slurry is coated on a metal foil, and dried to obtain a negative electrode sheet; The mass ratio of the active material, electrolyte, conductive agent and binder is 30-80:10-50:5-30:1-5.
10. An all-solid-state battery, comprising a lithium positive electrode sheet, an electrolyte Li6PS5Cl and a negative electrode sheet, characterized in that: The negative electrode sheet comprises the negative electrode sheet for the all-solid-state battery according to claim 8.
Citation Information
Patent Citations
Novel all-solid-state lithium ion battery
CN113363556A
Solid-state battery with silicon-based negative electrode
CN119029270A
Silicon-carbon negative electrode material with high mechanical strength
CN119133400A
Sulfide solid electrolyte, sulfide glass, electrode mixture material and lithium ion battery
JP2017117635A
Non-aqueous electrolytic solutions for lithium batteryand lithium ion secondary battery
KR1020040092425A